Kompetencje i zadania wojewody w zakresie przeciwdziałania zagrożeniom terrorystycznym na przykładzie województwa dolnośląskiego - Czudiak, Jakub (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The article examines the powers and tasks of governors in preventing terrorist threats as exemplified by the Lower Silesian Province. Every governor is a representative of the Council of Ministers in a given province. He or she is responsible for implementing government programmes in the region and for supervising government institutions operating in the region. An important area in which the governors carry out their tasks is broadly defined national security. In this respect the governors operate with the help of organisational units responsible for crisis management established at the provincial offi ces, provincial crisis management centres as well as advisory bodies, i.e. crisis management task forces. Prevention of terrorist threats is an element of the state’s internal security and the legislator has took this element into account in crisis management and assigned specific tasks to governors. Under the provisions of the Crisis Management Act the governors prevent, counteract and eliminate the effects of terrorist incidents, and cooperate in this respect with the head of the Internal Security Agency. Thus the governors are the authority which, in addition to various agencies and other institutions, are obliged to carry out specific tasks relating to terrorism prevention.
Keywords: administracja; zadania wojewody; zarządzanie kryzysowe; terroryzm; bezpieczeństwo narodowe; bezpieczeństwo międzynarodowe; zagrożenia bezpieczeństwa